INTEGRATED MARITIME DOMAIN INFORMATIONS AWARENESS - Sumali Morapitiya; Wiraj Leelarathna; Ruwan Bolongho (PREPARE@u® | IEI Conferences, 2021)
The centralized, integrated maritime domain informations awareness system (IMDIAS) is one of the most important and required information systems for a country covered by the sea. This paper presents detailed information on the implemented integrated maritime domain informations awareness system (IMDIAS) which is based on the most related informations for sea operations and Automatic Identification System (AIS), is used to collect the data to a central point from the selected 13 points to cover the complete sea area around the country. Using this system data of the ships and crafts which are plying the waters around the island can be viewed through a single interface. Detailed transmitted by the AIS system is received and collected from 13 points to the central point.  The implemented system is low cost and reduces the complexity of collecting information at the central point. Also, it is more beneficial to maritime operations and especially for the port authorities.